Ulasan Pelanggan Memediasi Brand Ambassador Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Kecantikan Scarlett Whitening Pada Mahasiswi Universitas Islam Malang Angkatan 2022 - Nimas Fahdiatur Riza; N. Rachma; Sulton Sholehuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study was conducted to examine the mediating role of customer reviews in the relationship between brand ambassador and product quality on purchase decisions of Scarlett Whitening beauty products among students of Universitas Islam Malang, class of 2022. The research employed an explanatory design, utilizing primary data collected through Likert-scale questionnaires distributed to 135 respondents selected via purposive sampling, as well as secondary data obtained from relevant scientific literature. Data analysis was carried out using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The findings reveal that brand ambassador, product quality, and customer reviews have a positive and significant effect on purchase decisions, while brand ambassador and product quality also positively influence customer reviews. Furthermore, customer reviews were found to play a significant mediating role, strengthening the influence of brand ambassador and product quality on purchase decisions. The implications of this study indicate that customer reviews serve as social validation and provide practical insights for companies to enhance the appeal of local beauty products. Keywords: Brand Ambassador, Product Quality, Customer Reviews, Purchase Decision, Scarlett Whitening